2005
DOI: 10.1021/jp055013j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Conformational Changes of O-Phenyl-cinchonidine:  A Theoretical and VCD Spectroscopy Study

Abstract: The conformational analysis of the synthetic chiral modifier O-phenyl-cinchonidine (PhOCD) used in enantioselective hydrogenations over noble metal catalysts has been performed at a PM3 semiempirical level in vacuum. The minimum energy conformations calculated at the DFT level with a medium-size basis set have been compared to those of the parent alkaloid cinchonidine (CD). PhOCD behaves similarly to CD and shows four main conformers, denoted as Closed(1), Closed(2), Open(3), and Open(4). Open(3) is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…118 More recently, they also reported a mixed VCD spectroscopy and computational study of O-phenyl cinchonidine. 119 Zaera and co-workers reported a mixed NMR and computational study of the effect of protonation of cinchonidine. 120 Lastly, Szöllösi and co-workers have reported a similar mixed study on the conformational behavior of py -hexahydrocinchonidine.…”
Section: Lewis/brønsted Base Catalysismentioning
confidence: 99%
“…118 More recently, they also reported a mixed VCD spectroscopy and computational study of O-phenyl cinchonidine. 119 Zaera and co-workers reported a mixed NMR and computational study of the effect of protonation of cinchonidine. 120 Lastly, Szöllösi and co-workers have reported a similar mixed study on the conformational behavior of py -hexahydrocinchonidine.…”
Section: Lewis/brønsted Base Catalysismentioning
confidence: 99%
“…[10,11] In this study, we use a unified first-principles methodology for all environments (gas phase clusters, molecules adsorbed on a rare-gas surface or embedded into a rare-gas matrix) to derive these interaction potentials and afterwards the vibrational and structural effects caused by clustering and embedding. [10,11] In this study, we use a unified first-principles methodology for all environments (gas phase clusters, molecules adsorbed on a rare-gas surface or embedded into a rare-gas matrix) to derive these interaction potentials and afterwards the vibrational and structural effects caused by clustering and embedding.…”
Section: Imentioning
confidence: 99%
“…[39] Therefore, combination of VCD experiments with theoretical VCD calculations is becoming an increasingly strong scientific instrument in the determination of absolute configuration [40][41][42] or conformation of chiral molecules. [43][44][45] Recently, it has been shown that the VCD method can also be a powerful tool in studying the intermolecular interactions of chiral molecules. [46,47] Continuing our previous study, [35] we undertook a detailed investigation on the conformation behavior of gas-phase cysteine isolated in low-temperature Ar and N 2 matrices.…”
Section: (Sh)cha C H T U N G T R E N N U N G (Nhmentioning
confidence: 99%